2024
DOI: 10.1088/1361-6560/ad4c4d
|View full text |Cite
|
Sign up to set email alerts
|

Transformer-CNN hybrid network for improving PET time of flight prediction

Xuhui Feng,
Amanjule Muhashi,
Yuya Onishi
et al.

Abstract: In positron emission tomography (PET) reconstruction, the integration of Time-of-Flight (TOF) information, known as TOF-PET, has been a major research focus. Compared to traditional reconstruction methods, the introduction of TOF enhances the signal-to-noise ratio (SNR) of images. Precision in TOF is measured by Full Width at Half Maximum (FWHM) and the offset from ground truth, referred to as coincidence time resolution (CTR) and bias. 
This study proposes a network combining Transformer and Convoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…One way to approach this circumstance is the usage of machine learning, which is given as classical learning systems (Naunheim et al 2023a) or neural networks (Chen and Liu 2021), with its capabilities to transcend traditional static or linear timestamp adjustments by providing event-by-event corrections. Recent research demonstrated the capabilities of using waveform information to improve CTR (Berg and Cherry 2018, Ai et al 2021, Onishi et al 2022, Feng et al 2024. In most cases, the researchers decided to use convolutional neural networks (CNNs) due to their ability to capture local patterns and invariance against shifts given by the architecture that exploits convolutional filters.…”
Section: Introductionmentioning
confidence: 99%
“…One way to approach this circumstance is the usage of machine learning, which is given as classical learning systems (Naunheim et al 2023a) or neural networks (Chen and Liu 2021), with its capabilities to transcend traditional static or linear timestamp adjustments by providing event-by-event corrections. Recent research demonstrated the capabilities of using waveform information to improve CTR (Berg and Cherry 2018, Ai et al 2021, Onishi et al 2022, Feng et al 2024. In most cases, the researchers decided to use convolutional neural networks (CNNs) due to their ability to capture local patterns and invariance against shifts given by the architecture that exploits convolutional filters.…”
Section: Introductionmentioning
confidence: 99%